(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Main principles of different types designing dams of ground materials, conditions of their application, calculation, peculiarities ofconstruction, operation, reconstruction and repairs, the requirements for the protection of natural environment are considers in article. Keywords:soil dam, building regulations.